Brain fMRI during orientation selective epidural spinal cord stimulation - Antonietta Canna (Nature Portfolio, 2021)
Abstract Epidural spinal cord stimulation (ESCS) is widely used for chronic pain treatment, and is also a promising tool for restoring motor function after spinal cord injury. Despite significant positive impact of ESCS, currently available protocols provide limited specificity and efficiency partially due to the limited number of contacts of the leads and to the limited flexibility to vary the spatial distribution of the stimulation field in respect to the spinal cord. Recently, we introduced Orientation Selective (OS) stimulation strategies for deep brain stimulation, and demonstrated their selectivity in rats using functional MRI (fMRI). The method achieves orientation selectivity by controlling the main direction of the electric field gradients using individually driven channels. Here, we introduced a similar OS approach for ESCS, and demonstrated orientation dependent brain activations as detected by brain fMRI. The fMRI activation patterns during spinal cord stimulation demonstrated the complexity of brain networks stimulated by OS-ESCS paradigms, involving brain areas responsible for the transmission of the motor and sensory information. The OS approach may allow targeting ESCS to spinal fibers of different orientations, ultimately making stimulation less dependent on the precision of the electrode implantation.